2021
DOI: 10.15376/biores.16.2.3797-3807
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulolytic activity of Pleurotus ostreatus under solid state fermentation using silage, stover, and cobs of maize

Abstract: Lignocellulolytic white-rot fungi allow the bioconversion of agricultural wastes into value-added products that are used in a myriad of applications. The aim of this work was to use corn residues (Zea mays L.) to produce valuable products under solid-state fermentation (SSF) with Pleurotus ostreatus. White-rot fungus P. ostreatus was isolated from maize silage (MS) and thereafter it was inoculated on MS as substrate and compared with maize stover (MSt) and maize cobs (MC) to determine the best lignocellulosic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…In addition to the biosafety of T. harzianum, its ability to produce multiple cellulolytic enzymes using different agricultural residues has been recognized and documented and it is often chosen as a good enzyme producer (Lee et al 2017;Abdel-Ghany and Bakri 2019;Asis et al 2021). The role of L. bulgaricus and enzyme extract Cellulolytic enzymes play a vital role in numerous industrial applications, and in the current study, cellulolytic enzymes were applied in order to enhance conditions that prevented the growth of undesirable fungi and their mycotoxins in maize silage indirectly through encouraging the proliferation of L. bulgaricus (Ganash et al 2021). Li et al (2020) mentioned that some lactic acid bacteria (LAB) might be able to minimize the lignin content in silage when amended with cellulase enzyme.…”
Section: Enzyme Productionmentioning
confidence: 97%
“…In addition to the biosafety of T. harzianum, its ability to produce multiple cellulolytic enzymes using different agricultural residues has been recognized and documented and it is often chosen as a good enzyme producer (Lee et al 2017;Abdel-Ghany and Bakri 2019;Asis et al 2021). The role of L. bulgaricus and enzyme extract Cellulolytic enzymes play a vital role in numerous industrial applications, and in the current study, cellulolytic enzymes were applied in order to enhance conditions that prevented the growth of undesirable fungi and their mycotoxins in maize silage indirectly through encouraging the proliferation of L. bulgaricus (Ganash et al 2021). Li et al (2020) mentioned that some lactic acid bacteria (LAB) might be able to minimize the lignin content in silage when amended with cellulase enzyme.…”
Section: Enzyme Productionmentioning
confidence: 97%
“…Membrillo et al (2008), Luna et al (2013), Méndez-Hernández et al ( 2018) y Ganash et al (2021) publicaron valores inferiores en la cuantificación de la actividad de lacasas que la cepa P15 con cinco días de fermentación sólida en olote del presente estudio. Membrillo et al (2008) reportaron 0.02 UI/g MS en bagazo de caña de azúcar (2.9 mm de tamaño de partícula) inoculado con P. ostreatus por ocho días; Luna et al (2013) cuantificaron 3.46 UI/g MS en una fermentación sólida de 12 días con rastrojo de cebada y P. ostreatus; mientras, Méndez-Hernández et al (2018) informaron una cuantificación de 1.4 y 4.1 U/g con una fermentación de cinco y diez días con rastrojo de maíz y Fomes sp; y Ganash et al (2021) publicaron 2.1 y 2.2 U/mL en rastrojo de maíz inoculado con P. ostreatus por cinco y diez días. Márquez et al (2007) mencionan que P. ostreatus presenta mayor actividad de lacasas (13.9 UI/g MS) que de celulasas (1.06 UI/g MS), lo que coincide con lo reportado en el presente estudio (Cuadros II y III).…”
Section: Actividad Enzimáticaunclassified
“…Márquez et al (2007) mencionan que P. ostreatus presenta mayor actividad de lacasas (13.9 UI/g MS) que de celulasas (1.06 UI/g MS), lo que coincide con lo reportado en el presente estudio (Cuadros II y III). Asimismo, la actividad enzimática de P. ostreatus varía según las condiciones del proceso de fermentación sólida: tipo de microorganismo a usar, el tiempo de la fermentación sólida, el tipo de sustrato y su tamaño de partícula, la afinidad enzima-sustrato (Kumar et al 2008, Sánchez-Santillán et al 2015b, Zárate-Salazar et al 2020, la composición de la pared celular del sustrato, la naturaleza del inóculo, la temperatura (Park et al 2002, Sánchez-Santillán et al 2015a, Zárate-Salazar et al 2020, la estructura de la planta utilizada (olote o totomoxtle; Luna et al 2013, Zárate-Salazar et al 2020, Ganash et al 2021) y las propiedades mecánicas y físicas de los sustratos (Ganash et al 2021 a,b,c Medias con diferente literal en la misma fila indican deferencias (p < 0.05). Celulasas = U/g, Lacasas = U/g, MS = g/kg MS, Ce = g/kg MS de cenizas, MO = g/kg MS de materia orgánica, FDN = g/kg MS de fibra detergente neutro, FDA = g/kg MS de fibra detergente ácido, Hemi = g/kg MS de hemicelulosa, PC = g/kg MS de proteína cruda, Cepa = MR y P15 de P. ostreatus, Sustrato = olote, totomoxtle y rastrojo de maíz, días = cinco y diez días de fermentación sólida, EEM = error estándar de la media.…”
Section: Actividad Enzimáticaunclassified
“…Currently, the number of studies that focus on the utilization of lignocellulosic substrates are increasing (Iwuagwu et al 2020;Nongthomban et al 2021). Ganash et al (2021) demonstrated that Pleurotus species are very effective in breaking down lignocellulosic residues making it a suitable mushroom to be cultivated on lignocellulosic substrates (Figure 1). This could be due to the type and quantity of enzymes including lignolytic, Table 1 The inclusion and exclusion criteria that have been conducted for this review paper.…”
Section: Cultivation and Analysis Of P Ostreatus Nutritional Contentmentioning
confidence: 99%